2021
DOI: 10.3390/ani11113026
|View full text |Cite
|
Sign up to set email alerts
|

Perches as Cooling Devices for Reducing Heat Stress in Caged Laying Hens: A Review

Abstract: Heat stress is one of the most detrimental environmental challenges affecting the biological process and the related production performance of farm animals, especially in poultry. Commercial laying hens have been bred (selected) for high egg production, resulting in increased sensitivity to heat stress due to breeding-linked metabolic heat production. In addition, laying hens are prone to heat stress due to their inadequate species-specific cooling mechanisms resulting in low heat tolerance. In addition, hens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The monoamines of NEP, EP, TRP, 5-HT and 5-HIAA of the raphe nuclei were analyzed using high performance liquid chromatography (UltiMateTM 3000 RSLCnano System, Thermo Fisher Scientific Inc., Waltham, MA, USA), following previously described procedures [64]. Briefly, each tissue was weighed and homogenized in ice-cold 0.2 M perchloric acid (PCA) at a 10:1 ratio.…”
Section: Central Monoaminesmentioning
confidence: 99%
“…The monoamines of NEP, EP, TRP, 5-HT and 5-HIAA of the raphe nuclei were analyzed using high performance liquid chromatography (UltiMateTM 3000 RSLCnano System, Thermo Fisher Scientific Inc., Waltham, MA, USA), following previously described procedures [64]. Briefly, each tissue was weighed and homogenized in ice-cold 0.2 M perchloric acid (PCA) at a 10:1 ratio.…”
Section: Central Monoaminesmentioning
confidence: 99%
“…Thus, the hematocrit value tends to decrease during egg laying due to the process of hemodilution, namely an increase in blood plasma volume and erythrocyte mass. Plasma levels return to normal when the last follicle ovulates (Hu et al, 2021).…”
Section: Blood Profilementioning
confidence: 93%
“…However, even under long-term or chronic heat stress, small improvements in the thermal environment have been reported to improve egg production and quality. For example, Hu et al [36,37] reported greater egg production, fewer cracked eggs, heavier eggs with greater breaking force, and especially shell thickness and eggshell percentage, for hens subjected to two years of heat stress but with cooled perches [38], compared to non-cooled or no perches.…”
Section: Temperature (mentioning
confidence: 99%